APAKAH RITME SIRKADIAN BERPENGARUH TERHADAP ANTIBIOTIKA : STUDI LITERATUR - Ilham alifiar; Nur Rahayuningsih; Lalu Muhammad Irham; Chita Widia (JFL : Jurnal Farmasi Lampung, 2022)
Antibiotics are one of the most widely used drugs in the world, therefore research on the use of antibiotics has been carried out, including research on the use of antibiotics associated with circadian rhythms for 24 hours. This literature study aims to explore research related to the effects of circadian rhythms on antibiotic drug levels. We conducted a search on two electronic databases, namely PubMed and Cochrane Library to search for articles related to the influence of circadian rhythms on antibiotics. This study does not limit the year, but the focus of this study is research conducted on humans and is a clinical study or randomized controlled clinical study. From the search, 28 articles were obtained from PubMed and 19 articles from the Cochrane Library. Of the total articles, six articles fall into the criteria of this study. One article is a test on levofloxacin, one article is a test on cefrozil, one article is a test on flomoxef, one article is a test on ciprofloxacin, and two articles are tests on tobramycin. From this study, it was found that the human body's circadian rhythm has an effect on antibiotics, either affecting the pharmacokinetic profile of the drug, or affecting the potential therapeutic effect of the antibiotic itself. Keywords: antibiotics, chronopharmacology, circadian rhythm